Hydrothermal Treatment (Htt) for Improving the Fuel Properties of Biomass Residues - Diaz-Robles, L (Springer Science and Business Media Deutschland GmbH, 2023)
Water leaching and hydrothermal carbonization are tools to upgrade biomass residues for combustion. Water leaching reduces the ash content, which increases the heating value, while hydrothermal carbonization (HTC) increases heating value and ash content and decreases the organic fraction of the fuel. The objective of this study is to investigate, whether low temperature hydrothermal treatment (HTT) of biomass residues can combine the positive aspects of both treatments and avoid the negative aspects: a decrease of the ash content (leaching) instead of an increase (HTC) and a strong increase of the heating value by deoxygenation (HTC) instead of a low increase by ash reduction (leaching). Sawdust, conifer bark, black locust bark, green cuttings, and leaves were treated at 150 °C, 170 °C and 185 °C in a batch reactor. The impact of the three treatments on combustion properties, inorganic element reduction, and organic compound formation in the liquid phase were investigated. All biomass residues, except sawdust treated at 150 °C, showed increased heating values and reduced ash contents. The intensity of the heating value increases, and the reduction rates of selected ash elements were discussed, including a comparison of literature values and a short review on organic reaction and formation processes at low temperature and pressure conditions. © 2022, The Author(s).